Modern Cardiac Surgical Outcomes in Nonagenarians: A Multicentre Retrospective Observational Study - Weinberg, Laurence; Walpole, Dominic; Lee, Dong Kyu; D'Silva, Michael; Chan, Jian Wen; Miles, Lachlan Fraser; Carp, Bradly; Wells, Adam; Ngun, Tuck Seng; Seevanayagam, Siven; Matalanis, George; Ansari, Ziauddin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background There have been multiple recent advancements in the selection, optimisation and management of patients undergoing cardiac surgery. However, there is limited data regarding the outcomes in nonagenarians, despite this cohort being increasingly referred for these interventions. The objective of this study was to describe the patient characteristics, management and outcomes of a cohort of nonagenarians undergoing cardiac surgery receiving contemporary peri-operative care. Methods After receiving ethics approval, we conducted a retrospective observational study of nonagenarians who had undergone cardiac surgery requiring a classic median sternotomy. All operative indications were included. We excluded patients who underwent transcatheter aortic valve implantation (TAVI), and surgery on the thoracic aorta via an endovascular approach (TEVAR). Patients undergoing TEVAR often have the procedure done under sedation and regional blocks with local anesthetic solution. There is no open incision and these patients do not require cardiopulmonary bypass. We also excluded patients undergoing minimally invasive mitral valve surgery via a videoscope assisted approach. These patients do not have a median sternotomy, have the procedure done via erector spinae block, and often are extubated on table. Data were collected from four hospitals in Victoria, Australia, over an 8-year period (January 2012–December 2019). The primary objective was to assess 6-month mortality in nonagenarian patients undergoing cardiac surgery and to provide a detailed overview of postoperative complications. We hypothesized that cardiac surgery in nonagenarian patients would be associated with a 6-month postoperative mortality <10%. As a secondary outcome, we hypothesized that significant postoperative complications (i.e., Clavien Dindo Grade IIIb or greater) would occur in > 30% of patients. Results A total of 12,358 adult cardiac surgery patients underwent surgery during the study period, of whom 18 nonagenarians (0.15%) fulfilled inclusion criteria. The median (IQR) [min-max] age was 91.0 years (90.0:91.8) [90–94] and the median body mass index was 25.0 (kg/m2) (22.3:27.0). Comorbidities, polypharmacy, and frailty were common. The median predicted mortality as per EuroSCORE-II was 6.1% (4.1:14.5). There were no cases of intra-operative, in-hospital, or 6-month mortality. One (5.6%) patient experienced two Grade IIIa complications. Three (16.7%) patients experienced Grade IIIb complications. Three (16.7%) patients had an unplanned hospital readmission within 30 days of discharge. The median value for postoperative length of stay was 11.6 days (9.8:17.6). One patient was discharged home and all others were discharged to an inpatient rehabilitation facility. Conclusion In this selected, contemporary cohort of nonagenarian patients undergoing cardiac surgery, postoperative 6-month mortality was zero. These findings support carefully selected nonagenarian patients being offered cardiac surgery (Trials Registry: https://www.anzctr.org.au/ACTRN12622000058774.aspx).